The Effects of Corporate Risk Management and Financial Flexibility on Firm Resilience in Indonesian Manufacturing Firms - Darmono Darmono; Siti Munawaroh; Sayugo Adi Purwanto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The period of 2020–2025 has been characterized by unprecedented global economic instability, placing the manufacturing sector under severe structural pressure and necessitating a comprehensive understanding of corporate resilience mechanisms. This study aims to investigate the integrative influence of corporate risk management and financial flexibility on the resilience of manufacturing firms in Indonesia. This study employs a quantitative causal-explanatory design to examine the relationships between corporate risk management, financial flexibility, and firm resilience in manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2020–2025. The sample was selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that corporate risk management and financial flexibility both have significant positive effects on firm resilience, while the relationship between corporate risk management and financial flexibility is not significant. These results imply that firms can strengthen resilience through effective risk management practices and strong financial flexibility independently, highlighting the importance of developing both strategies separately to enhance organizational stability during periods of economic uncertainty.